Pengembangan LKPD Berbasis Etnomatematika pada Cagar Budaya Selogending Lumajang untuk Memahami Konsep Bangun Ruang Sisi Datar - Widiyanto, Fifi Aleyda; Imamah Ah, Nurul; Wulandari, Christine (Polinomial : Jurnal Pendidikan Matematika, 2025)
The purpose of this research is to develop ethnomathematics-based Learner Worksheets (LKPD) on Selogending Lumajang cultural heritage to understand the concept of flat-sided spaces. This type of research is Research and Development (R&D) with a research model referring to the development of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this development research are students of class VII at SMP Negeri 01 Jatiroto with a total of 32 students. The instruments used in this research are interview sheets, and learner response questionnaire sheets. The results of data analysis of product validity from three experts scored 89.02% with “very valid” validation criteria. Based on the results of the assessment of the students' response questionnaire to assess the practicality of the LKPD, a score of 86.52% was obtained with the criteria “very practical”. And based on the results of the analysis of student learning outcomes test obtained an average percentage of effectiveness of 96.29% with a very effective category. So that the LKPD developed has met the criteria of valid, practical, and effective for use in learning.